Comparison of 60GHz CSRRs Ground Shield and Patterned Ground Shield On-chip Bandpass Filters Designed for 0.18μm CMOS Technology - Mat, D.A.A; Pokharel, R.K; Yoshida, K.; Kanaya, H. (The International Organization of Scientific Research, 2015)
This paper present on-chip open loop resonators 60GHz bandpass filters fabricated with the complementary metal-oxide semiconductor (CMOS) 0.18μm technology. Both filters have different ground shield placed at the lowest metal, M1. The first filter is designed with patterned ground shield below while the other filter with complementary split ring resonators (CSRR) as ground shield. The purpose of this research is to examine the best ground shield that can be used and employed to enhance the performance of the filter. Design simulation is conducted with electromagnetic simulator tools. It shows that, filter with CSRR as ground shield produce better results with S21= -2.682dB, 3-dB bandwidth = 10.8GHz compare to patterned ground shield with S21= -2.77dB, 3-dB bandwidth = 14GHz with both have good return loss.